Killing squirrels: Exploring motivations and practices of lethal wildlife management. (March 2018) - Crowley, Sarah L.; Hinchliffe, Steve; McDonald, Robbie A.
Wildlife management, pest control and conservation projects often involve killing nonhuman animals. In the United Kingdom, introduced grey squirrels Sciurus carolinensis are killed in large numbers to protect remnant populations of European red squirrels Sciurus vulgaris . Grey squirrels are also killed outside of red squirrel areas to protect broadleaved trees from squirrel damage, and as part of routine pest control, opportunistically, and sometimes recreationally. In order to investigate the ways in which this killing is conceived and practised in the United Kingdom, we conducted semi-structured interviews with practitioners and undertook participant observation of squirrel management activities, including lethal control. Analysing these field data, we identified important variations in practitioners' approaches to killing squirrels, and here we outline three 'modes of killing' – reparative/sacrificial, stewardship, and categorical – which comprise different primary motivations, moral principles, ultimate aims, and practical methods. We explore both productive alliances and possible tensions between these modes, and propose that clear, explicit consideration of how and why animals are both killed and 'made killable' should be a key component of any wildlife management initiative that involves lethal control.